High Reflectivity GaAs-based Photonic Crystal Reflectors for Cavity Optomechanics - Elkhouly, Karim (My University, 2019)
Cavity optomechanical devices couple light and mechanical motion. These devices enable reaching the quantum regime of mechanical motion, and thus, achieving the ultimate limits of sensing, and offer opportunities for hybrid quantum hardware. A current limitation in the field of cavity optomechanics is the weak coupling on the single photon level. Multi-element optomechanics has been proposed to enter the regime of strong coupling by enhancing the interaction strength in an array of high-reflectivity mechanical membranes placed inside a Fabry-Pérot cavity. This thesis investigates photonic crystal patterned GaAs-based single membrane devices, which constitute the building block of the multi-element optomechanical system. Homodyne detection was used for the mechanical characterization of GaAs membranes. Best performing devices achieved quality factors ~10^4. Furthermore, a mechanical mode tomography technique was developed, which allowed probing the mode shapes of the mechanical eigenmodes, and thus, comparing them to simulations. Photonic crystal patterns were designed to enhance the reflectivity of GaAs membranes. Optical characterization demonstrated devices with reflectivity > 98%. Moreover, unexpected Fano resonances appeared in the reflectivity spectrum. Rigorous coupled wave analysis was used to model the photonic crystal membrane, and it is shown that the parasitic feature is due to probing the membrane with a Gaussian beam of finite beam size. The feature is studied with respect to several physical parameters such as photonic crystal parameters, beam waist and beam polarization. The mechanical and optical properties shown in this thesis demonstrate the possibility of tuning the reflectivity of GaAs membranes, without degrading their mechanical properties. This is an important step towards the demonstration of a multi-element optomechanical system in the single-photon strong coupling regime based on GaAs membranes.
Keywords: quantum optics; optomechanics; quantum technology; experimental physics; applied physics